2013
DOI: 10.1002/jpln.201200652
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biochars produced from different feedstocks on soil properties and sunflower growth

Abstract: The use of biochar as a soil amendment is gaining interest to mitigate climate change and improve soil fertility and crop productivity. However, studies to date show a great variability in the results depending on raw materials and pyrolysis conditions, soil characteristics, and plant species. In this study, we evaluated the effects of biochars produced from five agricultural and forestry wastes on the properties of an organic‐C‐poor, slightly acidic, and loamy sand soil and on sunflower (Helianthus annuus L.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
93
4
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 231 publications
(140 citation statements)
references
References 33 publications
15
93
4
7
Order By: Relevance
“…The pore structure changes in the switchgrass biochars were similar to those in other lignocellulosic biochars (Xiao et al 2014). The biochar produced at 500 °C had a greater number of smaller pores and a larger surface area, which might enhance its performance as soil amendment and improve soil fertility (Alburquerque et al 2014;Liu et al 2016). Moreover, the small pores in the biochar may be conducive to bacterial and fungal colonization, and protect plants from being preyed on by soil fauna, such as protozoa (Warnock et al 2007).…”
Section: B500 B700mentioning
confidence: 74%
“…The pore structure changes in the switchgrass biochars were similar to those in other lignocellulosic biochars (Xiao et al 2014). The biochar produced at 500 °C had a greater number of smaller pores and a larger surface area, which might enhance its performance as soil amendment and improve soil fertility (Alburquerque et al 2014;Liu et al 2016). Moreover, the small pores in the biochar may be conducive to bacterial and fungal colonization, and protect plants from being preyed on by soil fauna, such as protozoa (Warnock et al 2007).…”
Section: B500 B700mentioning
confidence: 74%
“…The authors reported no changes in soil pH after applying Miscanthus biochar in lower doses (30 and 60 t ha -1 ). Also Alburquerque et al (2013) found that the application of wheat straw biochar in doses below 1% (30 t ha -1 ) in slightly acidic soil did not affect its pH. They observed a significant increase in the soil pH to the value of 8.5 only after applying a 225 t ha -1 dose of wheat straw biochar.…”
Section: Resultsmentioning
confidence: 96%
“…They observed a significant increase in the soil pH to the value of 8.5 only after applying a 225 t ha -1 dose of wheat straw biochar. However, Alburquerque et al (2013) argued that the biochar applied by them in doses of over 30 t ha -1 had a negative effect on the crop yield due to significantly increased electrical conductivity. The doses of organic materials applied in this study did not significantly increase electrical conductivity (EC) compared to the parameter value determined in the MF treatment (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This insignificant response on plant growth was probably associated with the insignificant improvement in nutrients uptake. The delayed effects of biochar on plant nutrients uptake (especially N, P and K) was likely due to temporary unavailability of nutrients for plant uptake (Lentz and Ippolito 2012) and N immobilisation when C:N ratio was above 16 (Alburquerque et al 2014;Walter and Rao 2015). The C:N ratio of EFB biochar was 93, and therefore, it potentially induced the immobilisation of mineral N. This was also supported by the observation in plant N, P, and K uptake, where the treatments with biochar showed no significant contribution in both 75 and 100% fertiliser rates.…”
Section: Discussionmentioning
confidence: 99%